PENGARUH KOMUNIKASI TERAPEUTIK PERAWAT TERHADAP KECEMASAN KELUARGA PASIEN YANG DIRAWAT DI RUANG INTENSIF - Siti " Aisyah; Gamya Tri Utami; Oswati " Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract The anxiety on patient’s family in intensive care were often caused by the failure of medication and treatment complications that ended in disability and death of the patients.This study aimed to determine the effect of therapeutic communication on patient’s family anxiety of hospitalized patients in intensive care. The study was "quasy experiment" by "Non-equivalent control group" design. The study was done in the ICU and Perinatology of Dumai Regional General Hospital. Total of samples were 30 respondents who had been taken by appropriate inclusion criteria and by using purposive sampling technic, respondents were divided into 15 respondents to experimental groups and 15 respondents to control group. The experimental group was given therapeutic communication  for 30 minutes and re-measured the anxiety scores 1 hour after the intervention. Measuring instruments which used in both groups were Zung-Self Rating Anxiety Scale questionnaires and observation sheet. The analysis used univariate analysis to see the frequency of respondent characteristics and for bivariate analysis by using dependent t-test and independent t test. The result showed that anxiety scores was decrease in the posttest of experimental group for 6.47 points. Statistical analysis showed significantly decreasing of anxiety by p value 0.005 (p <0.05). It was concluded that therapeutic communication could reduce the anxiety of patient’s family in intensive care. The results of this study recommends the nurses to improve the therapeutic communication to patients and patient’s family to reduce the anxiety which could  improve the quality of hospital’s service. Keywords: Therapeutic Communication, anxiety, patient's family, intensive care